No difference in the 24-hour interstitial fluid glucose profile with modulations to the glycemic index of the diet. - Aston, L; Laccetti, R; Mander, A; Hall, R; Moore, C; Jebb, SA (2010)
OBJECTIVE: Reducing the glycemic index (GI) of the diet may decrease metabolic risk, primarily through reduction and stabilization of blood glucose. The objective of this research was to investigate whether incorporation of lower or higher GI foods into mixed meals had different effects on daylong glucose profiles, measured in interstitial fluid by a continuous glucose-monitoring system. METHODS: The study was a randomized, balanced, two-way crossover intervention of 2 x 1-wk periods of lower and higher GI diets. Participants were 12 overweight healthy adult women (mean body mass index +/- standard deviation 27.5+/-2.3 kg/m(2)). Changes in GI were achieved through substitution of key staple carbohydrate-rich foods. After a 4-d run-in on each dietary regimen, participants wore the continuous glucose-monitoring system over 2 d of identical controlled feeding in the laboratory, separated by 1 d of ad libitum consumption at home. RESULTS: On controlled days, diets differed in GI by 15 U and provided equal energy, macronutrients, and fiber. On ad libitum days, diet diaries revealed a difference in GI of 14+/-1 U (mean +/- standard error), with no detectable difference in energy, macronutrient, or fiber intake. No differences were observed in glucose profiles between higher and lower GI interventions in the controlled or ad libitum setting. There was significant agreement in area under the glucose curve on repeated controlled feeding days (intraclass correlation 0.75). CONCLUSION: This study indicates that a difference in dietary GI of 14-15 U is insufficient to alter daylong glycemia as measured in interstitial fluid by the continuous glucose-monitoring system.